The influence of internship satisfaction and the psychological contract on the career identity behavior of fresh graduates - Feng, Ying; Zhang, Zhuo; Zeng, Xiuzhen; Liu, Yuying (Frontiers in Psychology, 2023)
Introduction Frequent resignation of young workers brings huge costs to the organizational management of enterprises. The frequent turnover behavior is a sign of low career identity, and exploring the paths that influence career identity behaviors is necessary. Previous studies have found that internship satisfaction and the psychological contract can influence career identity behavior. However, the dimensions of the psychological contract are unclear, and it is uncertain whether internship satisfaction can influence career identity behavior through the different dimensions of the psychological contract. This study attempts to expand the concept of psychological contract and construct a multiple mediation model. It aims to analyze the mediating role of different dimensions of the psychological contract between internship satisfaction and career identity behavior. Methods A sample survey was conducted on Chinese fresh graduates by way of the questionnaire survey, and a total of 576 valid questionnaires were collected. Amos 26.0 was used to analyze the data and verify the multiple mediation model. Results The results showed that psychological contract can be divided into three dimensions: transactional contract, relational contract, and developmental contract. Internship satisfaction can positively influence career identity behavior via the three dimensions of psychological contract, and there are differences in mediating effects among the dimensions. The mediating effect of developmental contract is the highest, relational contract is the second, and transactional contract is the lowest. Discussion This article expands the dimensions of psychological contract, emphasizes the importance of developmental contract, contributes to the literature on organizational psychology, and provides scales and empirical evidence for future research. The analysis points out that fresh graduates with long-term development opportunities often show higher career identity behavior. This provides valuable insights for enhancing career identity behavior, improving career sustainability, and assisting organizations in managing human resource mobility.